El Asesor Jurídico, una revista popular de jurisprudencia en vísperas de la Revolución (México, 1907-1909) - Daniela Marino (Caravelle)
The purpose of this paper is to determine whether the written culture was winning recognition within the traditional personal mediation made by small-town actors in the resolution of conflicts. Therefore, we will analyze a gazette created by lawyers interested in spreading legal and administrative knowledge to actors of small cities and towns, as well as to support rural communities in the handling of procedures and administrative forms to achieve success in their agrarian affairs.